2006
DOI: 10.1523/jneurosci.2623-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Memory and Synaptic Plasticity Are Impaired in a Mouse Model of Rett Syndrome

Abstract: Loss-of-function mutations or abnormal expression of the X-linked gene encoding methyl CpG binding protein 2 (MeCP2) cause a spectrum of postnatal neurodevelopmental disorders including Rett syndrome (RTT), nonsyndromic mental retardation, learning disability, and autism. Mice expressing a truncated allele of Mecp2 (Mecp2 308 ) reproduce the motor and social behavior abnormalities of RTT; however, it is not known whether learning deficits are present in these animals. We investigated learning and memory, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
451
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(494 citation statements)
references
References 36 publications
37
451
3
3
Order By: Relevance
“…VNS, if paired with the appropriate regimen of behavioral exposure or cognitive training, may represent a potential intervention to improve these disorders. Plasticity is a core deficit in many postnatal developmental disorders, including autism and forms of mental retardation [106][107][108][109]. Rehabilitative therapies do provide benefits in patients with postnatal developmental disorders.…”
Section: Potential Applications For Other Cognitive and Psychiatric Dmentioning
confidence: 99%
“…VNS, if paired with the appropriate regimen of behavioral exposure or cognitive training, may represent a potential intervention to improve these disorders. Plasticity is a core deficit in many postnatal developmental disorders, including autism and forms of mental retardation [106][107][108][109]. Rehabilitative therapies do provide benefits in patients with postnatal developmental disorders.…”
Section: Potential Applications For Other Cognitive and Psychiatric Dmentioning
confidence: 99%
“…[131][132][133][134] Electrophysiological studies from MeCP2 transgenic mice reported reduced neuronal activity in cortical 135 and hippocampal 136 neurons, suggesting that a shift in the balance between inhibition and excitation could be responsible for rapid motor, behavioural and cognitive regression typical of ReS. 137 MeCP2-deficient mice have attenuated ability to express LTP in the hippocampus 136,138 and in the motor and somatosensory cortex. 138 Importantly, the gene encoding BDNF is under MeCP2 regulation, 139 and the progression of symptoms in MeCP2-deficient mice seems to be correlated with gradually decreasing levels of circulating BDNF.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…79 The mutant mice have also been characterized by deficits in long-term social memory, observed following the repeated presentation of a juvenile mouse across several days. 80,81 Other behavioral abnormalities in Mecp2 308/y mice include deficits in nest building and other home cage activity, alterations in diurnal motor patterns, 79 and impaired learning and memory. 81 An abnormal phenotype is still observed when the loss of Mecp2 is limited to forebrain areas and to postnatal development.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…80,81 Other behavioral abnormalities in Mecp2 308/y mice include deficits in nest building and other home cage activity, alterations in diurnal motor patterns, 79 and impaired learning and memory. 81 An abnormal phenotype is still observed when the loss of Mecp2 is limited to forebrain areas and to postnatal development. 75,80 In particular, the conditional Mecp2-null mice still show forelimb and hindlimb clasping, motor impairment and ataxic gait, and decreased social preference.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%